Answer: -2x^2 (3x^2 + 8)
Step-by-step explanation: a^b+c =a^b a^c
1) -16x^2 - 6x^ x^2
2) Rewrite -16 as -2 * 8
2.a Rewrite -6 as -2 * 3
= -2 * 8x^2 - 2 * 3x^2x^2
3) facter out common term: -2x^2
= ur answer
Answer:
g[f(n)] = -8n+3
Step-by-step explanation:
Given,
g(n) = 2n + 5 , f(n) = -4n-1
Find g(f(n)),
Solutions,
g[f(n)] = g[-4n-1]
= 2(-4n-1) + 5
= -8n–2+5
g[f(n)] = -8n+3
Final Answer = g[f(n)] = -8n+3.
The formula for that area would be A=1/2xbxh so you would do A=1/2x3.5x3 and that equals 5.25
Answer:
The resultant of two forces of 7N and 3N acting at a right angle to one another is √58 N.
Step-by-step explanation:
Let the magnitude of the force of 7N be denoted as “F₁” on the x-axis and the magnitude of the force of 3N be denoted as “F₂” on the y-axis.
We are given that the two forces make an angle of 90° to one another as shown in the figure attached below.
Also, in the figure, we can see that the resultant force is denoted as “F”.
Now,
The magnitude of the resultant force can be calculated by using the Pythagoras theorem,
∴ F = √[F₁² + F₂²]
⇒ F = √[7² + 3²]
⇒ F = √[49 + 9]
⇒ F = √[58] N
Answer:
517
Step-by-step explanation:
The radius of a circle is just half of the diameter (1/2d = r)
1034/2 = 517